The Predation Behaviour of Fictor composticola on Parasitic Nematodes of Button Mushroom, Agaricus bisporus - Keshari, Nishi; Kanwar, R. S. (International Journal of Bio-resource and Stress Management, 2021)
In this study, the predation behaviour of male and female predatory nematode, Fictor composticola,was studied on five prey nematode species, Aphelenchus avenae, Aphelenchoides swarupi, Ditylenchus myceliophagus, Bursilla sp. and Panagrolaimus sp., found in the white button mushroom compost. The period of the study is of six months. The data recorded on number of encounters, part of the body of prey attacked, stage of the prey attacked, duration of feeding etc. The strike rate and prey susceptibility were calculated. The average number of encounters on all the five preys done by female F. composticola was 3.0 and that of the male was 6.0. Male F. composticola had more number of encounters on the prey nematode species than the females. Both the sexes preferred juvenile stages over adults as prey. The most attacked part by both females and males predator, was the posterior part of the prey body. In 80% of cases, female predators fed on the first encountered prey while males attacked the first encountered prey in 30% of cases only. The strike rate of female F. composticola was more (78.6%) than the male (48.2%). Mycophagous nematodes were more susceptible to predator’s attack than the microbivorous nematodes. The strike rate of the predator on different prey nematode species was found more on mycophagous nematodes than on microbivorous nematodes and minimum on Panagrolaimus sp. The average feeding duration of female F. composticola was 8 min and 31 sec and in the case of males it was 4 min and 11 sec.